(untitled) (University Heart Journal, 2011)
Nebivolol is a vasodilating β-blocker, which can be distinguished from other β-blockers by its haemodynamic profile. It combines β-adrenergic blocking activity with a vasodilating effect mediated by the endothelial Larginine nitric oxide (NO) pathway. The blood pressure lowering effect of nebivolol is linked to a reduction in peripheral resistance and an increase in stroke volume and preservation of cardiac output. Clinical trials have demonstrated that nebivolol reduces blood pressure similarly to atenolol, bisoprolol, amlodipine, nifedipine, lisinopril, and hydrochlorothiazide. The tolerability of nebivolol is similar to or better than that of these agents. In general, response rates to treatment are higher and the frequency and severity of adverse events are either comparable or lower with nebivolol. Endothelium-derived NO is important in the regulation of large arterial stiffness, which in turn is a major risk factor for cardiovascular disease. Therefore, antihypertensive drugs, such as nebivolol, that also improve endothelial function and decrease arterial stiffness, may contribute to a reduction in cardiovascular risk. Key words: Vasodilating β-blocker; nitric oxide (NO); peripheral resistance; arterial stiffness DOI: 10.3329/uhj.v6i2.7254 University Heart Journal Vol. 6, No. 2, July 2010 pp.93-96